148k views
1 vote
Select the correct answer. If f(x)=x^1/2-x and g(x)=2x^3-x^1/2-x, find f(x) − g(x).

2 Answers

5 votes

Answer:

(f-g)(x) = 2√x - 2x³

Explanation:

Write out the terms of f(x) as they are and then the negatives of all the terms of g. We get:

(f-g)(x) = √x - x - 2x³ + √x + x

Combining like terms, we get:

(f-g)(x) = 2√x - 2x³

User Talisa
by
5.5k points
3 votes

Answer:

2( √x - x³ )

Explanation:

see attached.

Select the correct answer. If f(x)=x^1/2-x and g(x)=2x^3-x^1/2-x, find f(x) − g(x-example-1
User Rhyek
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.